Can patients contribute to enhancing the safety and effectiveness of test‐result follow‐up? Qualitative outcomes from a health consumer workshop. (2nd December 2020) - Thomas, Judith; Dahm, Maria R.; Li, Julie; Georgiou, Andrew
Abstract: Background: Missed test‐results and failure to follow‐up test‐results are major patient safety concerns. Strategies to improve test‐results management have predominantly focused on clinician‐based interventions, with patients principally involved in studies of test‐result communication preferences, the impact of patient portals or experiences with reporting processes in primary care. Objective: To identify consumer perspectives and experiences of the challenges they have faced with test‐results management, through consumer participation in qualitative data analysis. Design and participants: Volunteers (n = 10) were recruited to participate in a health consumer reference group workshop on test‐results management. Prior to the workshop, consumers selected topics for discussion using a preference poll. During the workshop, consumers participated in qualitative data analysis of de‐identified excerpts of previously collected interview data discussing hospital test‐results management. Researchers (n = 5) guided consumers through the analytical process and discussion of themes. Discussions were audio‐recorded and transcribed for qualitative analysis. Results: Consumer‐selected topics for discussion were 'Transitions of Care' and 'Access'. Consumer data analysis prompted broader discussion including lived experiences. Following the workshop, a second level of content analysis pinpointed issues with implications for patient safety highlighting that consumers were astutely aware of macrolevel ' Systems Factors' relating to ' Emergency Departments' and the health system, as well as microlevel ' Patient Factors' (eg patient preferences and circumstances) which impact a patient's understanding during the ' Communication' (clinician to patient/between clinicians) of test‐results ' Information' (or lack thereof). Conclusions: Consumers identified the challenges patients experience with test‐results management, and our findings highlight areas for potential improvement in patient safety. Patient or public contribution: Ten health consumer volunteers actively participated in the test‐results management data analysis workshop conducted in this study. Two health consumers also volunteered to read and comment on the draft manuscript.